Ecological effects of cell-level processes: genome size, functional traits and regional abundance of herbaceous plant species - Herben, Tomás; Suda, Jan; Klimesová, Jitka; Mihulka, Stanislav; Ríha, Pavel; Símová, Irena (Annals of botany, 2012)
BACKGROUND AND AIMS: Genome size is known to be correlated with a number of phenotypic traits associated with cell sizes and cell-division rates. Genome size was therefore used as a proxy for them in order to assess how common plant traits such as height, specific leaf area and seed size/number predict species regional abundance. In this study it is hypothesized that if there is residual correlation between genome size and abundance after these traits are partialled out, there must be additional ecological effects of cell size and/or cell-division rate. METHODS: Variation in genome size, plant traits and regional abundance were examined in 436 herbaceous species of central European flora, and relationships were sought for among these variables by correlation and path analysis. KEY RESULTS: Species regional abundance was weakly but significantly correlated with genome size; the relationship was stronger for annuals (R(2) = 0·145) than for perennials (R(2) = 0·027). In annuals, genome size was linked to abundance via its effect on seed size, which constrains seed number and hence population growth rate. In perennials, it weakly affected (via height and specific leaf area) competitive ability. These relationships did not change qualitatively after phylogenetic correction. In both annuals and perennials there was an unresolved effect of genome size on abundance. CONCLUSIONS: The findings indicate that additional predictors of regional abundance should be sought among variables that are linked to cell size and cell-division rate. Signals of these cell-level processes remain identifiable even at the landscape scale, and show deep differences between perennials and annuals. Plant population biology could thus possibly benefit from more systematic use of indicators of cell-level processes.
Keywords: Plant Leaves; Genome Size; Cell Division; DNA, Plant; Ecology; Phylogeny; Chromosomes, Plant; Magnoliopsida; Phenotype; listy rostlin; Genome, Plant; Cell Size; Ploidies; Seeds; ploidie; délka genomu; fylogeneze; fenotyp; Czech Republic; DNA rostlinná; databáze nukleových kyselin; Databases, Nucleic Acid; ekologie; velikost buňky; chromozomy rostlin; Česká republika; genom rostlinný; semena rostlinná; buněčné dělení